SOSIALISASI MENGENAI MANFAAT VITAMIN A DI SD NEGERI 1 KALIMATI - Fika Quba Mayada; Gigih Kenanga Sari (LPPM AN Nuur, 2022)
Background: Vitamin A is a micronutrient that has very important benefits for the human body, especially in human vision. As is known, Vitamin A was the first fat-soluble vitamin to be discovered. In general, vitamin A is a generic name that states all retinoids and precursors/provitamin A/carotenoids which have biological activity as retinol. Method: Information about the benefits of vitamin A is provided in the form of educational and outreach activities (counseling) to students at SD Negeri 1 Kalimati. Results: There are 25 students in 1 class who know the benefits of vitamin A. Conclusion: students' awareness of drinking and eating foods containing vitamin A at SD Negeri 1 Kalimati.